Comparative Study of Murabahah and Istishna' Contracts in BTN Syariah Jombang Mortgage Loans - Amin Awal Amarudin; Muhamad Agil; Naily El Muna (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
Housing is a basic human need, so that sharia housing financing needs to be assessed for its compliance with sharia principles. This study aims to describe the implementation of Murabahah and Istishna’ contracts in Sharia Home Ownership Credit (KPR) products at Bank BTN KCPS Jombang and analyze the SWOT aspects of both contracts. The study uses a descriptive qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman model. The results of the study indicate that the Murabahah lil Amri bi Syira’ contract in the BTN Sejahtera iB KPR product is in accordance with the DSN-MUI Fatwa No. 04/DSN-MUI/IV/2000. The Istishna’ contract in the BTN Indent iB KPR product has also been implemented in accordance with the DSN-MUI Fatwa No. 06/DSN-MUI/IV/2000 and No. 09/DSN-MUI/IV/2000. A SWOT analysis shows that the murabahah contract excels in installment certainty and margin transparency, but has weaknesses in the disbursement process. Meanwhile, the Istishna' contract excels in home design flexibility, but faces the risk of construction specification discrepancies.